[11C]Carbon monoxide: advances in production and application to PET radiotracer development over the past 15 years - Carlotta Taddei; Victor W. Pike (SpringerOpen, 2019)
Abstract [11C]Carbon monoxide is an appealing synthon for introducing carbon-11 at a carbonyl position (C=O) in a wide variety of chemotypes (e.g., amides, ketones, acids, esters, and ureas). The prevalence of the carbonyl group in drug molecules and the present-day broad versatility of carbonylation reactions have led to an upsurge in the production of this synthon and in its application to PET radiotracer development. This review focuses on the major advances of the past 15 years.